Dissecting the mechanism of growth inhibition and tumour reversion mediated by oocyte extract in human breast cancer cells - Saad, Norazalina (2016)
Axolotl oocyte extract (AOE) has the ability to reprogram the breast cancer cell epigenome by modifying DNA methylation and histone modifications at the promoter region of silenced tumour suppressor genes, resulting in loss of cellular tumourigenicity (Allegrucci et al., 2011). The present study aimed to determine the signalling pathways and associated chromatin modifications involved in tumour reversion mediated by AOE in an attempt to identify specific oocyte molecules responsible for the reprogramming of breast cancer cells. Microarray analysis of reprogrammed tumours revealed a cell cycle block that was confirmed by BrdU labelling of xenograft tumours. The phenotype was recapitulated in vitro cultures up to 4 days after reprogramming, with AOE-treated cells showing a significant decreased entry in S phase of the cell cycle. Reduced expression of JUN and up-regulation of CDKN1B (p27) were measured, together with a reduction of phosphorylation of p44/42 MAPK signalling pathway. CDKN1B protein also showed a nuclear localisation in reprogrammed tumour xenografts compared to untreated controls. The reprogramming of breast cancer cells at genome-wide level was associated with a decrease in H3K9me2, H3K9me3 and H4K20me1 and in increase in H3K4me3, H3K27me3, H3K9Ac, H4K20me2 and H4K20me3 immediately after reprogramming (6 hours) and the pattern of changes was generally maintained at the time point of injection into xenografts (12 hours after reprogramming). Specific histone modifiers inhibitors were used during AOE treatment to dissect histone modification activities during cells reprogramming. Altogether, the results obtained suggest that axolotl oocytes contain complex activities that may cooperate to remodel the epigenetic and signalling landscape of breast cancer cells leading to reversion of malignancy by inducing cell cycle arrest and a state of quiescence. Therefore, this work has the potential to develop new therapeutic approaches based on oocyte molecules that could be tested in different types of breast cancer, especially those with poor prognosis and patient outcome.